Comparison the behavior of ZnO–NP–AC and Na, K doped ZnO–NP–AC for simultaneous removal of Crystal Violet and Quinoline Yellow dyes: Modeling and optimization. (15th September 2019) - Karimi, R.; Yousefi, F.; Ghaedi, M.; Rezaee, Z.
Graphical abstract: Abstract: Zinc oxide nanoparticle loaded on activated carbon (ZnO–NP–AC) in presence and absence of Na and K doping were prepared and fully characterized using different techniques such as SEM and XRD analysis. Then, this material was used for simultaneous ultrasound-assisted removal of Quinoline Yellow (QY) and Crystal Violet (CV) from aqueous solution. QY and CV removal percentage toward various parameters including pH, adsorbent mass, their initial concentration and sonication time were examined by central composite design (CCD) and best operational conditions achieved at 7 and 15 mg L −1 of QY and CV, 0.02 g ZnO–NP–AC, pH of 7 and 4 min sonication. The artificial neural networks (ANN) are applied to predict of dyes adsorption onto present adsorbent and the obtained results have good agreement with experimental data. The absolute average deviations (AADs) of QY and CV dyes adsorption onto ZnO–NP–AC with experimental data are 1.11 and 1.06, and the linear regression between the network outputs and the result and targets were established to be reasonable based on acceptable determination coefficient ( R 2 ) of 0.994 and 0.974, respectively. Also, the kinetic models and adsorption equilibrium isotherm investigation revealed the well fit of the experimental data to second-order kinetic model with constant rate value of 0.086 and 0.206 and Langmuir isotherm with maximum monolayer capacity ( q Max ) of 37.49 and 75.39 mg g −1 at optimum conditions for QY and CV removal onto ZnO–NP–AC.